Pelatihan Pembuatan Pupuk Eco-Enzyme Sebagai Alternatif Pengelolaan Sampah Organik Rumah Tangga Di Desa Kedunglumpang Jombang - M Qoyum Zuhriawan; Fitri Umardiyah; Sinta Pramudita (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Waste from each house can have an impact on the quantity of waste in that area. One solution to reduce this waste is to utilize household waste into useful products, namely by turning the waste into Eco-enzyme fertilizer. This activity was carried out in Kedunglumpang village, Mojoagung sub-district, Jombang district. The training participants included the PKK and IPNU IPPNU organizations in Kedunglumpang Village, totaling 30 people. Based on the pretest given to participants, it was found that almost 70% of participants did not know about the use of organic waste. After participating in this Pkm training, participants were given a posttest and found that 100% of the participants knew, understood and were enthusiastic about applying Eco-enzyme fertilizer production from organic waste